A Review on Various Formulation Methods in preparing Colon targeted mini-tablets for Chronotherapy - Mohd Abdul Hadi, N. G. Raghavendra Rao, A. Srinivasa Rao, Tayyaba Mahtab, Sayeeda Tabassum (Journal of Applied Pharmaceutical Science, 2018)
Rheumatoid arthritis disease, according to its circadian rhythms shows early morning peak symptoms. Sometimes, single unit (ex. larger tablets) and multiple units (ex. granules, pellets) colon targeted drug delivery systems are not always an efficient treatment option. Because single unit larger tablets may possess the disadvantages of unintentional disintegration of the formulation due to GI variation or manufacturing deficiency leading to complete dose dumping. Even the multiple unit drug delivery systems such as granules and pellets also have many drawbacks because of their irregular weights, shapes and sizes. Thus, a tight, reproducible in-vitro and in-vivo release profile can’t be achieved. In an attempt to overcome the problems presented by these delivery systems, advanced system such as multiple unit mini-tablets have developed. This is an approach towards achieving critical factors such as better patient compliance and convenience. In the present review, a concerted try has made to summarize the details of different formulation methods used in preparing mini-tablets of lornoxicam and naproxen drugs for colon targeted delivery in chronotherapy. The techniques formulated and evaluated as core-mini-tablets filled pulsincap drug delivery system (using time dependent polymers), matrix-mini-tablets filled capsule drug delivery system (using microsomal enzyme dependent and pH dependent polymers) and coated-mini-tablets filled capsule drug delivery system (using pH dependent polymers). All these methods were successful in targeting Anti-inflammatory drugs at colonic junction. Hence, the mentioned formulation methods can be successfully used in the chronotherapeutic treatment of Rheumatoid arthritis.
Keywords: Core-mini-tablets filled pulsincap drug delivery system, Matrix-mini-tablets filled capsule drug delivery system, Coated-mini-tablets filled capsule drug delivery system.